Judi Slot Mematikan, Bagaimana Hubungan Gambling Related Cognition dan Perceived Social Support Dengan Gambling Behavior - Faradea Rahmatun; Nurul Isnaini; Annisa Annisa (Universitas Kristen Maranatha, 2025)
Online slot gambling is very hightighted issue today. Online slot gambling is played by many people, even children, and many are caught up in this online slot gambling game. This study aims to test the correlation between gambling-related cognition and perceived social support, which is predicted to correlate with gambling behavior. This study uses a quantitative approach with a correlational method. This study involved 361 online slot gambling players. Data analysis using Structural Equation Model-Partial Least Square (SEM-PLS). The hypothesis test results indicate that gambling-related cognition is positively correlated with gambling behavior, with t = 27.466 (t > 1.96) and p = 0.000 (p < 0.005), supporting the first hypothesis. However, perceived social support does not significantly correlate with gambling behavior, with t = 1.062 (t < 1.96) and p = 0.288 (p > 0.005), leading to the rejection of the second hypothesis. These findings can be a reference for further research with the same theme and can be used as a reference in developing interventions to reduce gambling behavior.